Mental health among UK university staff and postgraduate students in the early stages of the COVID-19 pandemic. Issue 4 (21st October 2021) - Carr, Ewan; Davis, Katrina; Bergin-Cartwright, Gabriella; Lavelle, Grace; Leightley, Daniel; Oetzmann, Carolin; Polling, Catherine; Stevelink, Sharon A M; Wickersham, Alice; Razavi, Reza; Hotopf, Matthew
Abstract : Objectives: To characterise the baseline King's College London Coronavirus Health and Experiences of Colleagues at King's cohort and describe patterns of probable depression and anxiety among staff and postgraduate research students at a large UK university in April/May 2020. Methods: An online survey was sent to current staff and postgraduate research students via email in April 2020 (n=2590). Primary outcomes were probable depression and anxiety, measured with the Patient Health Questionnaire-9 and Generalised Anxiety Disorder-7, respectively. Secondary outcomes were alcohol use and perceived change in mental health. Outcomes were described using summary statistics and multivariable Poisson regression was used to explore associations with six groups of predictors: demographics and prior mental health, living arrangements, caring roles, healthcare, occupational factors and COVID-19 infection. All analyses were weighted to account for differences between the sample and target population in terms of age, gender, and ethnicity. Results: Around 20% of staff members and 30% of postgraduate research students met thresholds for probable depression or anxiety on the questionnaires. This doubled to around 40% among younger respondents aged <25. Other factors associated with probable depression and anxiety included female gender, belonging to an ethnic minority group, caregiving responsibilities and shielding or isolating. Around 20% of participants were found to reach cut-off for hazardous drinking on Alcohol Use Disorders Identification Test, while 30% were drinking more than before the pandemic. Conclusions: Our study shows worrying levels of symptoms of depression, anxiety and alcohol use disorder in an occupational sample from a large UK university in the months following the outbreak of the COVID-19 pandemic.